Bacterial etiology of Keratitis and their antimicrobial susceptibility pattern at a tertiary care hospital. - Akhtar, Fahd Kamal; Saleem, Zubair; Malik, Muna; Chaudhry, Adeel; Sajjad, Ayesha; Rehan, Abdul Mudabbir (Pakistan Journal of Ophthalmology, 2020)
Purpose: The aim of this study was to find out Bacterial etiology and antimicrobial susceptibility pattern of bacteria causing infective keratitis at a tertiary care hospital of Lahore Study Design:Descriptive cross sectional study Study Place and Study Period: PGMI/AMC/LGH, Lahore, in 2015 - 2018. Sample Collection: Non-probability convenience sampling Material and Methods: The corneal scrapings taken by the ophthalmologist was immediately inoculated on Chocolate agar, Blood agar and MacConkay agar culture plates with the help of sterilized wire loop in the operation theater.These plates were taken to laboratory for incubation and further microbiological processing. After inoculating on the culture agar plates, the scrapings from cornea were smeared on glass slides with the help of sterilized wire loop. The smears were air-dried stained with Gram’s stain, Kinyoun stain and Giemsa stain. The culture and staining were further processed for microbiological analysis of bacterial etiology and antimicrobial susceptibility. Results:7 of each cases of Staphylococcus aureus and Streptococcus pneumoniae were isolated accounting 28% of total bacteria. Gram negative bacteria are relatively sensitive to all groups of antibiotics as compared to Gram positive bacteria who were resistant of major groups of antibiotic like Fluoroquinolones and aminoglycosides. Conclusion: We concluded that a cumulative antimicrobial data should be published from laboratory on antimicrobial susceptibiblity pattern of bacterial keratitis for its empirical treatment.